\(\sqrt{56}-2\sqrt{98}-5\sqrt{18}-\sqrt{63}+2\sqrt{28}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

14 tháng 10 2018

3 căn 56 nha

15 tháng 10 2018

\(3\sqrt{56}-2\sqrt{98}-5\sqrt{18}-\sqrt{63}+2\sqrt{28}=3\sqrt{4.14}-2\sqrt{49.2}-5\sqrt{9.2}-\sqrt{9.7}+2\sqrt{4.7}=3.2\sqrt{14}-2.7\sqrt{2}-5.3\sqrt{2}-3\sqrt{7}+2.2\sqrt{7}=6\sqrt{14}-14\sqrt{2}-15\sqrt{2}-3\sqrt{7}+4\sqrt{7}=6\sqrt{14}-29\sqrt{2}+\sqrt{7}\)

16 tháng 7 2017

\(3\sqrt{50}-2\sqrt{98}-5\sqrt{18}-\sqrt{63}+2\sqrt{28}\)

\(=15\sqrt{2}-14\sqrt{2}-15\sqrt{2}-3\sqrt{7}+4\sqrt{7}\)

\(=-14\sqrt{2}-3\sqrt{7}+4\sqrt{7}\)

\(=-14\sqrt{2}+\sqrt{7}\)

20 tháng 6 2018

a) \(3\sqrt{8}-4\sqrt{18}+5\sqrt{32}-\sqrt{50}=3\sqrt{4.2}-4\sqrt{9.2}+5\sqrt{16.2}-\sqrt{25.2}=6\sqrt{2}-12\sqrt{2}+20\sqrt{2}-5\sqrt{2}=9\sqrt{2}\)b) \(\left(15\sqrt{50}+5\sqrt{200}-3\sqrt{450}\right):10=\left(15\sqrt{50}+5\sqrt{50.4}-3\sqrt{50.9}\right):10=\left(15\sqrt{50}+10\sqrt{50}-9\sqrt{50}\right):10=\dfrac{16\sqrt{50}}{10}=\dfrac{16\sqrt{25.2}}{10}=\dfrac{80\sqrt{2}}{10}=8\sqrt{2}\) c) \(2\sqrt{28}+2\sqrt{63}-3\sqrt{175}+\sqrt{112}=2\sqrt{7.4}+2\sqrt{7.9}-3\sqrt{7.25}+\sqrt{7.16}=4\sqrt{7}+6\sqrt{7}-15\sqrt{7}+4\sqrt{7}=-\sqrt{7}\)

d)
\(\left(\sqrt{14}-3\sqrt{2}\right)^2+6\sqrt{28}=14-2.3\sqrt{2.14}+18+6\sqrt{28}=32-6\sqrt{28}+6\sqrt{28}=32\)

17 tháng 10 2022

b: \(\Leftrightarrow\sqrt{25x-75}=x+3\)

=>25x-75=x^2+6x+9 và x>=-3

=>x^2+6x+9-25x+75=0 và x>=-3

=>x^2-19x+84=0 và x>=-3

=>\(x\in\varnothing\)

c: \(\Leftrightarrow x+1+4\cdot3x+4\sqrt{3x\left(x+1\right)}=64\)

=>\(4\sqrt{3x\left(x+1\right)}=64-12x-x-1=-13x+63\)

=>\(48x\left(x+1\right)=\left(-13x+63\right)^2\)

=>\(48x^2+48x=169x^2-1638x+3969\)

=>x=1323/121 hoặc x=3

17 tháng 7 2018

\(a.6\sqrt{3}-2\sqrt{12}+5\sqrt{300}-7\sqrt{243}=6\sqrt{3}-4\sqrt{3}+50\sqrt{3}-63\sqrt{3}=\left(6-4+50-63\right)\sqrt{3}=-11\sqrt{3}\)

\(b.\sqrt{28}+3\sqrt{63}-6\sqrt{175}-\dfrac{1}{5}\sqrt{252}=2\sqrt{7}+9\sqrt{7}-30\sqrt{7}-\dfrac{6}{5}\sqrt{7}=\left(2+9-30-\dfrac{6}{5}\right)\sqrt{7}=-20,2\sqrt{7}\)\(c.5\sqrt{44}-2\sqrt{275}-3\sqrt{176}=10\sqrt{11}-10\sqrt{11}-12\sqrt{11}=-12\sqrt{11}\)

\(d.2\sqrt{75}-\sqrt{12}+2\sqrt{147}-7\sqrt{103}=10\sqrt{3}-2\sqrt{3}+14\sqrt{3}-7\sqrt{103}=22\sqrt{3}-7\sqrt{103}\)

17 tháng 7 2018

\(a.6\sqrt{3}-2\sqrt{12}+5\sqrt{300}-7\sqrt{243}=6\sqrt{3}-4\sqrt{3}+50\sqrt{3}-63\sqrt{3}=-11\sqrt{3}\)

\(b.\sqrt{28}+3\sqrt{63}-6\sqrt{175}-\dfrac{1}{5}\sqrt{252}=2\sqrt{7}+9\sqrt{7}-30\sqrt{7}-\dfrac{6}{5}\sqrt{7}=-\dfrac{101}{5}\sqrt{7}\)

\(c.5\sqrt{44}-2\sqrt{275}-3\sqrt{176}=20\sqrt{11}-10\sqrt{11}-12\sqrt{11}=-2\sqrt{11}\)

\(d.2\sqrt{75}-\sqrt{12}+2\sqrt{147}-7\sqrt{103}=10\sqrt{3}-2\sqrt{3}+14\sqrt{3}-7\sqrt{103}=22\sqrt{3}-7\sqrt{103}\)